2012
DOI: 10.1287/moor.1120.0551
|View full text |Cite
|
Sign up to set email alerts
|

Online Stochastic Matching: Online Actions Based on Offline Statistics

Abstract: We consider the online stochastic matching problem proposed by Feldman et al. [4] as a model of display ad allocation. We are given a bipartite graph; one side of the graph corresponds to a fixed set of bins and the other side represents the set of possible ball types. At each time step, a ball is sampled independently from the given distribution and it needs to be matched upon its arrival to an empty bin. The goal is to maximize the number of allocations.We present an online algorithm for this problem with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(70 citation statements)
references
References 13 publications
(32 reference statements)
0
69
1
Order By: Relevance
“…due to [19]. We take a step towards closing that gap by showing that an algorithm can achieve 0.7299 > 1 − 2e −2 for both the unweighted and vertex-weighted variants with integral arrival rates.…”
Section: Overview Of Vertex-weighted Algorithm and Contributionsmentioning
confidence: 99%
See 2 more Smart Citations
“…due to [19]. We take a step towards closing that gap by showing that an algorithm can achieve 0.7299 > 1 − 2e −2 for both the unweighted and vertex-weighted variants with integral arrival rates.…”
Section: Overview Of Vertex-weighted Algorithm and Contributionsmentioning
confidence: 99%
“…Constraint 3 is valid because each vertex in V has an arrival rate of 1. Constraint 4 is used in [19] and [12]. It captures the fact that the expected number of matches for any edge is at most 1 − 1/e.…”
Section: Lp Benchmark For Deterministic Rewardsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mahdian and Yan [14], in 2011, achieved a competitive ratio of 0.696. Manshadi et al [16] showed that you cannot do better than 0.823. If the problem also has weights, then the bestpossible competitive ratio is 0.368 by a reduction from the secretary problem as shown by Kesselheim et al [11].…”
Section: Related Workmentioning
confidence: 99%
“…The theory of matching started with Peterson and König and was under a lot of interests in graph theory with problems like maximum matchings. It was extended to online matching setting [8,12,14] where one population is static and the other arrives according to a stochastic process. In the recent years, fully dynamic matching models have been considered where both populations are random.…”
Section: Introductionmentioning
confidence: 99%